Building Student Character Through Pancasila Learning with an Interactive Visual Approach - Bella Ayu Kusumahati; Suudin Aziz (Agrapana Media, 2026)
The main problem in teaching Pancasila values in elementary schools is the use of learning methods that are less varied and lack concrete media, resulting in students being less active, quickly bored, and character values not yet optimally internalized in daily life. This study aims to analyze the application of interactive visual media in Pancasila learning and its contribution to character building among students at SDN Mori 1 Trucuk. Using a descriptive qualitative approach, this study examines how visual media such as animations, illustrations, and interactive displays enhance students' understanding of Pancasila values and encourage positive behavioral changes. Data were collected through classroom observations, interviews with teachers, the principal, and students, as well as documentation of learning activities. The results of the study show that before the use of interactive visual media, Pancasila learning was still conventional, with students mostly memorizing without internalizing the values. After using interactive visual media, students showed higher engagement, stronger understanding, and more positive character behaviors such as cooperation, discipline, and mutual respect. Teachers and principals stated that visual media makes abstract concepts more concrete and easier to relate to students' daily lives. This study concludes that interactive visual media is very effective in supporting cognitive understanding as well as character development in accordance with the values of Pancasila.